Pink gold: transformation of backwater aquaculture on Goa's Khazan lands - Rubinoff, Janet Ahner (2001)
This paper explores recent economic and environmental changes in what had been an ecologically balanced subsistence production system in Goan coastal villages and, in particular, the socio-economic forces behind this reversal of productive strategies. In part, these local productive choices and their environmental impact are rooted in global economic forces and markets, seemingly far removed from the backwaters of Goa. Although there are many interrelated dimensions of this transformation, the author focuses on the growing importance of backwater pisciculture at the expense of agriculture and the fragile khazan environment. - Reproduced
Keywords: Aquaculture - India - Goa; Aquaculture